Repellent efficacy of DEET, Icaridin, and EBAAP against Ixodes ricinus and Ixodes scapularis nymphs (Acari, Ixodidae) - Büchel, Kerstin; Bendin, Juliane; Gharbi, Amina; Rahlenbeck, Sibylle; Dautel, Hans (Ticks and tick-borne diseases, 2015)
Repellent efficacy of 10% EBAAP (3-[N-butyl-N-acetyl]-aminopropionic acid, ethyl ester) and 10% Icaridin ((2-(2-hydroxyethyl)-1-piperidinecarboxylic acid 1-methylpropyl ester)) were evaluated against 20% DEET (N,N-diethyl-3-methylbenzamide) in human subject trials against ticks. Responses of host-seeking nymphs of the European castor bean tick (Ixodes ricinus L.; Acari: Ixodidae) and the North American blacklegged tick (I. scapularis Say; Acari: Ixodidae) were compared. Tests were carried out according to the US-EPA standard protocol with ethanolic solutions of the active ingredients of repellents being applied to the forearm of 10 volunteers. The upward movement of ticks was monitored until repellent failure taking up to 12.5 h. Application of 20% DEET resulted in median complete protection times (CPT; Kaplan-Meier median) between 4 and 4.5 h, while 10% EBAAP yielded CPTs of 3.5-4h. No significant differences were found between the efficacies of two repellents nor between the two species tested. The median of the CPT of a 10% Icaridin solution was 5h in nymphs of I. scapularis, but 8h in those of I. ricinus (P<0.01). Based on these studies, EBAAP and Icaridin are efficacious alternatives to DEET in their repellent activity against nymphs of the two Ixodes ticks with Icaridin demonstrating particularly promising results against I. ricinus. Future research should investigate whether similar results occur when adult Ixodes ticks or other tick species are tested.